The role of microRNAs in the therapeutic action of D-cycloserine in a post-traumatic stress disorder animal model: an exploratory study. (August 2017) - Malan-Müller, Stefanie; Fairbairn, Lorren; Hart, Stephanie; Daniels, Willie M.U.; Jalali Sefid Dashti, Mahjoubeh; Kidd, Martin; Seedat, Soraya; Gamieldien, Junaid; Hemmings, Sîan M.J.
Abstract : Objectives: Post-traumatic stress disorder is characterized by impaired fear extinction and excessive anxiety. D-Cycloserine (DCS) has previously been shown to facilitate fear extinction and decrease anxiety in animal and human studies. This study utilized a contextual fear-conditioning animal model to investigate the involvement of microRNAs (miRNAs) in fear extinction and the reduction of anxiety, as mediated by the co-administration of DCS and behavioural fear extinction. Methods: Fear conditioning consisted of an electric foot shock; fear extinction consisted of behavioural fear extinction co-administered with either DCS or saline. The light/dark avoidance test was used to evaluate anxiety-related behaviour subsequent to fear conditioning and was used to evaluate anxiety-related behaviour following fear conditioning and to subsequently group animals into well-adapted and maladapted subgroups. These subgroups also showed significant differences in terms of fear extinction. Small RNAs extracted from the left dorsal hippocampus were sequenced using next-generation sequencing to identify differentially expressed miRNAs associated with DCS-induced fear extinction and reduction of anxiety. In-silico prediction analyses identified mRNA targets (from data of the same animals) of the differentially expressed miRNAs. Two of the predicted mRNA–miRNA interactions were functionally investigated. Results: Overall, 32 miRNAs were differentially expressed between rats that were fear conditioned, received DCS and were well adapted and rats that were fear conditioned, received saline and were maladapted. Nineteen of these miRNAs were predicted to target and regulate the expression of 63 genes differentially expressed between fear-conditioned, DCS-administered, well-adapted and fear-conditioned, saline-administered, and maladapted groups (several of which are associated with neuronal inflammation, learning and memory). Functional luciferase assays indicated that rno-mir-31a-5p may have regulated the expression of interleukin 1 receptor antagonist ( Il1rn ) and metallothionein 1a ( Mt1a ). Conclusion: These differentially expressed miRNAs may be mediators of gene expression changes that facilitated decreased neuronal inflammation, optimum learning and memory and contributed towards effective fear extinction and reduction of anxiety following the co-administration of DCS and behavioural fear extinction. Abstract : Supplemental Digital Content is available in the text.